Taxonomic revision of the genus Glypthelmins Stafford, 1905 (Platyhelminthes: Digenea: Plagiorchiida), parasites of anurans in the Americas - Razo-Mendivil, U.; de León, G. Pérez-Ponce (Zootaxa, 2008)
The phylogeny of the genus Glypthelmins has previously been examined using molecular data. Based on those results, congeneric species can now be defined by a combination of phylogenetic, morphological and geographical criteria. The 10 putative congeneric species (G. quieta, G. californiensis, G. facioi, G. shastai, G. pennsylvaniensis, G. hyloreus, G. intestinalis, G. brownorumae, G. tuxtlasensis, and G. parva) form a monophyletic group. In this work, morphological descriptions are provided for these 10 species, including a full list of synonymies, diagnoses, hosts, geographic distributions and details of specimen deposition in museum collections, comments on their life cycles, and references to gene sequences deposited in GenBank. An amended diagnosis of the genus and a key to identify the species is presented, based on a combination of morphological traits.